KAJIAN SIFAT FISIKOKIMIA DAN ORGANOLEPTIK HIDROLISAT TEMPE HASIL HIDROLISIS PROTEASE [Study on physicochemical and organoleptic properties of tempeh hydrolysate produced by protease] - Achmad Subagio; Siti Hartanti; Wiwik Siti Windrati; . Unus; Mukhammad Fauzi; Bambang Herry (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Physicochemical and organoleptic properties of tempeh hydrolysate produced by protease were studied. The tempeh hydrolysate had different properties comparing with those of the unhydrolyzed tempeh powder. Hydrolysis of the tempeh protein could lower the antioxidant activity. Accordingly, the TBA value increased significantly when the tempeh was hydrolyzed by protease. This process also promoted Maillard reaction, resulting in a more brown color than that of the unhydrolyzed tempeh powder. Moreover, the tempeh hydrolysate had a better protein solubility, and a higher index of umami taste by organoleptic evaluation.